Opposition Politics and International Crises: A Formal Model4. Issue 4 (10th June 2014) - Shea, Patrick; Teo, Terence K.; Levy, Jack S.
<x xml:space="preserve">Abstract</x> Democratic foreign policy choices are a function of expected international outcomes and the preferences, power, and information of domestic actors. Studies of domestic political competition and international crisis bargaining have argued that an opposition's policy positions send credible signals of the government's intentions to adversarial target states. This paper contends that while opposition behavior may send informative signals, it can also directly constrain the policy options of the government. We relax previous assumptions that the opposition cannot directly prevent war or influence the outcomes of war (Schultz 2001). Instead, we assume that the opposition controls some political resources and attempts to influence the government's policy decisions in a way that advances its own partisan interests. To empirically demonstrate the theoretical differences in our model in comparison with previous domestic opposition models, we examine the case of the Quasi‐War of 1798 between the United States and France.